Manden eller bolden? Om værdier, politik og deliberativt demokrati - Loftager, Jørn (Politik, 2010)
The concept of „new politics“ with its focus on values and identities has won widespread acceptance. However, there are serious reasons to doubt its adequacy. On the basis of well-founded classical sociological accounts it can be seen how it conceals the fact that values and identities have always been important aspects of politics. Likewise, the concept and discourse of „new politics“ tends to ignore the social problem-solving dimension of politics, and consequently it fails to pay due attention to both the particular role and identity of the citizen evolving in modern society and to democracy as deliberative democracy.